2022
DOI: 10.3390/children9070938
|View full text |Cite
|
Sign up to set email alerts
|

Strength and VO2max Changes by Exercise Training According to Maturation State in Children

Abstract: The health benefits of physical activity (PA) are widely recognized; however, biological maturation contributions are a subject that has been little studied, which is why the aim of this study was to analyze the effect of a six-week training program at moderate-intensity on the muscular strength and aerobic capacity in children between nine and 13 years (13 ± 1.0 years) according to their maturation state. Twenty-six schoolchildren (15 girls) participated in a six-week physical exercise program based on aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
3
0
4
Order By: Relevance
“…This finding has been supported by prior studies examining the connection between aerobic exercise and handgrip strength. These studies have shown that sedentary individuals who engage in less aerobic exercise are at a higher risk of experiencing reduced handgrip strength [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding has been supported by prior studies examining the connection between aerobic exercise and handgrip strength. These studies have shown that sedentary individuals who engage in less aerobic exercise are at a higher risk of experiencing reduced handgrip strength [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…В литературе длительное время обсуждался вопрос о повышении аэробных возможностей у детей, находящихся в препубертатном и пубертатном периодах возрастного развития [4][5][6][7][8]. Отмечалось, что нагрузки, развивающие выносливость, в эти периоды не приводят к повышению аэробной мощности, либо приводят к незначительному улучшению пикового потребления кислорода (не более 5-6 %), что связано с гормональным статусом детей [6].…”
Section: Age-related Features Of Aerobic Ability In Athletes Doing En...unclassified
“…Отмечалось, что нагрузки, развивающие выносливость, в эти периоды не приводят к повышению аэробной мощности, либо приводят к незначительному улучшению пикового потребления кислорода (не более 5-6 %), что связано с гормональным статусом детей [6]. Однако опыт подготовки юных спортсменов, специализирующихся в циклических видах спорта, и современные научные исследования [4,5,7,8] убедительно свидетельствуют о вы-соких способностях детей к увеличению аэробной работоспособности.…”
Section: Age-related Features Of Aerobic Ability In Athletes Doing En...unclassified
See 1 more Smart Citation
“…However, several factors, such as ponderal status, sex, maturation, and basal fitness may affect the intervention effectiveness. For example, a recent study by Enríquez-del-Castillo et al (2022) shows how the state of maturation can play a role in modulating changes in physical fitness following an exercise program in children [ 15 ]. However, the difference between different age groups during youth and the influence that gender has on the effectiveness of an exercise program in overweight young people is currently unclear.…”
Section: Introductionmentioning
confidence: 99%